Diagnostic accuracy of the Mini-Balance Evaluation Systems Test (Mini-BESTest) in screening for fall risk among individuals with vestibular disorders - Nichaporn Khumduang; Kanokporn Pooranawatthanakul; Nattawan Utoomprurkporn; Akkradate Siriphorn (PLoS ONE, 2026)
Vestibular disorders significantly impair postural stability and elevate fall risk, necessitating the use of validated assessment tools. While the Mini-Balance Evaluation Systems Test (Mini-BESTest) is a comprehensive measure of balance, diagnostic cut-off scores tailored to the vestibular population remain poorly defined. This study aimed to evaluate the diagnostic accuracy of the Mini-BESTest in identifying fall risk among individuals with vestibular disorders. Forty-two participants underwent assessment using the Mini-BESTest, 4-Meter Walk Test (4MWT), and Timed Up and Go (TUG) test. Fall risk was classified using a dual-criteria approach: (1) fall history and severity (e.g., injury, frequency, and frailty) and (2) physical performance benchmarks on the 4MWT and TUG. Participants were subsequently categorized into low or intermediate-to-high fall risk groups. Accuracy was determined via receiver operating characteristic (ROC) curve analysis. The results yielded an Area Under the Curve (AUC) of 0.69, indicating poor-to-modest discriminatory ability. At the optimal cut-off score of ≤ 23, the scale demonstrated high sensitivity (92.3%) and low specificity (44.8%), resulting in a positive likelihood ratio (LR+) of 1.67 and a negative likelihood ratio (LR-) of 0.17. Exploratory subscore analysis revealed that only the reactive postural control domain provided significant discriminatory trends under bootstrap analysis (95% CI: 0.516–0.823). These results suggest that while the comprehensive total score of Mini-BESTest remains the necessary standard for primary risk stratification due to the scale’s validated unidimensional design, reactive postural control performance represents a key underlying physiological driver of instability in this population. Recognizing this specific domain impairment can better assist clinicians in tailoring targeted, individualized therapeutic interventions during vestibular rehabilitation.